Subsolidus phase relations in Ca2Mo2O8?NaEuMo2O8-powellite solid solution predicted from static lattice energy calculations and Monte Carlo simulations - Vinograd, V.; Bosbach, D.; Winkler, B.; Gale, Julian (Royal Society of Chemistry, 2008)
Thermodynamic mixing properties and subsolidus phase relations of Ca2Mo2O8?NaEuMo2O8powellites were modelled in the temperature range of 423?1773 K with static lattice energy calculations based on empirically constrained interatomic potentials. Relaxed static lattice energies (SLE) of a large set of randomly varied structures in a 4 4 2 supercell of I41/a powellite (a = 5.226 A , c = 11.433 A ) containing 128 exchangeable (Ca, Na and Eu) atoms were calculated using the general utility lattice program (GULP). These energies were cluster expanded in the basis set of 69 pair-wise effective interactions and three configuration-independent parameters. Temperature-dependent enthalpies of mixing were calculated using the Monte Carlo method. Free energies of mixing were obtained by thermodynamic integration of the Monte Carloresults. The simulations suggest that the NaEuMo2O8 end-member is nearly fully ordered and has I4 symmetry. The calculated subsolidus temperature-composition phase diagram is dominated by three miscibility gaps which are separated by narrow fields of stability of two ordered phases with the compositions of x = 4/9 and x = 2/3, where x is the mole fraction of the NaEuMo2O8 end-member.